READING DESCRIPTIVE TEXT COMPREHENSION IMPROVEMENT BY JOGSAW TEACHING TECHNIQUE - Puspa Rini; Nur Ekaningsih (Universitas Muria Kudus, 2020)
The goal of this research was to decide how effective jigsaw improved the comprehension ability of reading descriptive text of class X students of Sultan Agung 1 Semarang Islamic High School in 2018/2019 academic year in understanding descriptive text. This research type was on a quasi-experimental design. The Senior High School students gade tenth as the population of this study which divided into two groups, X IPS 1 class developed as group of class control and X IPS 2 served as the group of experimental. The way to gather some data, Pre-test and post were used to evaluate the students’ competence. Grounded on the results of the study, the mean score of pretest done in the control class was in the average of 52.93, while on the experimental class was happened 53.06. Treatment was implemented on the experiment class in about four times while the control class was educated by conservative teaching. After implementing four times of treatment, the mean score of the post-test of the control class rose up by 60.17. Accordingly, the post-test mean of the experimental class in the average score of 70.32. Based on the results of data analysis showed that there was a significant difference because of the T-test indicating that sig (2-tailed) showed in the number 0.000. Briefly, Ho was rejected but H1 was accepted. This means that jigsaw was operative to enhance reading comprehension ability of the students. Hence, Using jigsaw in understanding descriptive text could give better comprehension in students' reading skillsKeywords: Jigsaw, Reading Comprehension, Descriptive Text